Individual versus Village Lending: Evidence from Montenegro. Issue 4 (1st February 2017) - Beck, Thorsten; Behr, Patrick
Abstract: This paper analyzes differences in loan performance across two Montenegrin microfinance institutions with different lending techniques using a sample of individuals borrowing from both institutions. We make use of administrative data from both institutions over the period 2004–2013. While one institution relies on village associations for screening and monitoring of borrowers, the other institution uses the individual liability approach. We find that the likelihood to go into arrears is higher for the institution with a strictly individual lending technique, while the likelihood of going into arrears over 30 days is higher for the institution working with village associations. These results are robust to a variety of additional tests, including different definitions of arrears and subsamples. Our findings suggest that the institution using an individual lending technique provides certain flexibility to its clients, while the village‐based microfinance institution might face more strategic default behavior. We provide evidence that once a borrower is in arrears, (s)he is more likely to stay in arrears for more than 30 days in branches with a higher share of borrowers in arrears and in the village‐based lender. Our findings provide evidence that a village‐ or group‐based lending technique is not necessarily superior to the individual lending technique in terms of loan performance.